Demokrasi dan Sisi Gelapnya: Pengalaman dari Eropa, Afrika, Asia dan Amerika Latin - Daniel Hutagalung (Budapest International Research and Critics University, 2019)
Article explains that there is a view that democracy and violence often go hand in hand, and the point at which democratic states decide to use violence is merely subjective, and is a matter of political decision, and not ethical necessity. This is indeed a difficult thing to accept in the context of democracy, even though it is more representative of a realistic calculation or consideration that encourages politicians or the government in deciding whether or not to use violence. Indonesia's future seems full of uncertainty, because liberal and socialist influence continues to diminish, while secularism continues to be battered by the rise of political Islamization. This is especially true if the country weakens and a number of political factions carry out radicalization.